2022
DOI: 10.1136/bmjopen-2021-055938
|View full text |Cite
|
Sign up to set email alerts
|

Reopening strategies, mobility and COVID-19 infections in Europe: panel data analysis

Abstract: ObjectivesCharacterise the reopening policies of European countries after the first wave of infections and evaluate how these policies affected economic activity and subsequent infections.Study designUsing publicly available data, we construct a database of reopening policy announcements by country authorities and develop measures related to the speed and timing of reopening. Using panel data regressions, we then assess how a country’s reopening action subsequently affected its mobility and COVID-19 infections… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
12
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 23 publications
(19 reference statements)
3
12
0
1
Order By: Relevance
“…These findings augment the existing research on the benefits of mask-wearing 1 , 23 , 24 and reopening policy 6 , 25 , 26 by emphasizing the COVID-19 trends associated with lifting mask mandates in Iowa in spring 2021. The results were in contrast to studies of Texas where lifting the mask mandate and reopening did not seem to be associated with an increase in mobility or infections.…”
Section: Discussionsupporting
confidence: 56%
See 3 more Smart Citations
“…These findings augment the existing research on the benefits of mask-wearing 1 , 23 , 24 and reopening policy 6 , 25 , 26 by emphasizing the COVID-19 trends associated with lifting mask mandates in Iowa in spring 2021. The results were in contrast to studies of Texas where lifting the mask mandate and reopening did not seem to be associated with an increase in mobility or infections.…”
Section: Discussionsupporting
confidence: 56%
“…These results were consistent with findings on the association of introducing mask mandates in Kansas 8 and reopening decisions in the United States 29 and across Europe. 6 Our findings added a more nuanced understanding of the mechanism by showing that while mask-wearing was reduced, mobility of people did not increase. The results suggested that containment policies such as mask mandates should be kept in place at least until population immunity through widespread vaccinations is achieved.…”
Section: Discussionmentioning
confidence: 62%
See 2 more Smart Citations
“…Inzwischen liegen für die im Rahmen der SARS-CoV-2-Pandemie implementierten Wiedereröffnungsstrategien erste länderspezifische Analysen vor [ 16 ]. Im Bereich der Unterhaltungs- und Event-Industrie existieren derzeit lediglich mathematische Vorhersagemodelle [ 2 , 41 ] sowie die im Pandemieverlauf veröffentlichten Handlungsoptionen und Rahmenkonzepte mit Teilbereichen aus dem Infektions- und Arbeitsschutz [ 28 ].…”
unclassified